2015
DOI: 10.1007/s10342-014-0859-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of components of the leaf area distribution on drag relations for Cryptomeria japonica and Chamaecyparis obtusa

Abstract: The objectives of this study were to clarify the effects of components of the leaf area distribution on the drag coefficient of crowns and streamlining (e.g., leaf area index; LAI, outline of the crown shape, and clumpiness) and to contribute to the accumulation of data on drag relations by quantifying data for Chamaecyparis obtusa and Cryptomeria japonica. We conducted drag experiments while simultaneously capturing dynamic crown images for 28 Ch. obtusa crowns and 13 Cr. japonica crowns to analyze the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…At the same time, the mean base overturning moment coefficients decrease for larger wind speeds, which is discussed further in Section 3.2. This result is also found in wind tunnel tests of broad-leaved species (Cao, et al, 2012;Vollsinger, et al, 2005) and field measurements of broadleaved species (Kitagawa, et al, 2015;Koizumi, et al, 2010).…”
Section: Mean Base Overturning Momentssupporting
confidence: 76%
See 1 more Smart Citation
“…At the same time, the mean base overturning moment coefficients decrease for larger wind speeds, which is discussed further in Section 3.2. This result is also found in wind tunnel tests of broad-leaved species (Cao, et al, 2012;Vollsinger, et al, 2005) and field measurements of broadleaved species (Kitagawa, et al, 2015;Koizumi, et al, 2010).…”
Section: Mean Base Overturning Momentssupporting
confidence: 76%
“…There are two main methods to study aerodynamic characteristics of trees. One is field measurements, which have mainly focused on the aerodynamic force coefficients (Grant and Nickling, 1998;Kane and Smiley, 2006;Kitagawa et al, 2015;Koizumi et al, 2010Koizumi et al, , 2016Borisevich and Vikhrenko, 2018;Gonzales et al, 2018) and overall capacity (Gillies et al, 2000;Kane et al, 2008). Estimated aerodynamic forces acting on tree crowns obtained from field measurements are of value; however, are rarely conducted because of the obvious challenge.…”
Section: Introductionmentioning
confidence: 99%
“…For the LAI value 1.5, the "C d " value was 0.015. This increment of "C d " with LAI was due to clumping character of the green gram canopy (Kitagawa et al, 2015).…”
Section: Drag Coefficientmentioning
confidence: 87%
“…In case of natural turbulent boundary layer, where the temperature gradient is small and having uniform density, the wind profile follows a log law (Dong et al, 2001). The leaf area index, leaf area distribution affect the drag coefficient of different crops (Kitagawa et al, 2015). Masseroni et al (2015) observed a close correlation between the height of the rice crop with "d" and "Z 0 ".…”
mentioning
confidence: 99%
“…However, the wind speed profiles used are virtual and averaged, such as the logarithmic model [ 7 ], which does not express temporal changes of the wind profile. Determination of the drag coefficient is difficult and impractical for use in a forest stand; the drag coefficient of a tree changes with wind speed, crown morphology, and tree species in wind tunnel experiments [ 8 12 ] and large variation within individuals are observed in natural winds [ 9 ].…”
Section: Introductionmentioning
confidence: 99%